Can industry-education integration enhance enterprise employee safety and health levels? - Huiling Chen; Chengcheng Zhu; Zhao Cheng; Jie Feng; Boya Zhao (Frontiers in Public Health, 2025)
IntroductionHarmonious relationships between enterprises and employees are key to sustainable enterprise development. Therefore, the study explores whether industry-education integration can enhance enterprise employee safety and health levels, in order to alleviate enterprise labor-management issues.MethodsBased on panel data from Chinese A-share listed enterprises between 2012 and 2021, this study employs a quasi-natural experiment using China’s pilot program for industry-education integrated enterprises. A difference-in-differences model is constructed to examine how this novel employee training model affects enterprise employee safety and health levels.ResultsThis study finds that, first, industry-education integration promotes an increase in enterprise employee safety and health. Second, the mechanism behind this effect lies in enhancing enterprise internal control systems and strengthening media oversight. Third, this effect is more pronounced in state-owned enterprises and enterprises with stronger management capabilities. Fourth, industry-education integration also drives improvements in enterprise technological innovation.DiscussionThis study provides evidence of the positive impact of this new training model on enterprise development and offers corresponding policy recommendations.